A yeast-based high-throughput screen identifies inhibitors of trypanosomatid HRG heme transporters with potent leishmanicidal and trypanocidal activity - Cabello-Donayre, María; Cabello-Donayre, Irene; Guerra, Diego; Orrego, Lina M.; Morales, Juan C.; Cautain, Bastien; Vicente, Francisca; Pérez-Victoria, José M. (International Journal of Antimicrobial Agents, 2025)
Objectives: New drugs are required to treat neglected diseases caused by trypanosomatid parasites such as Leishmania, Trypanosoma brucei and Trypanosoma cruzi . An Achilles’ heel of these parasites is their heme auxotrophy; they have an absolute dependence on scavenging this molecule from the host, and trypanosomatid HRG heme transporters (TrypHRG) play an important role in this process. As these pro- teins are essential for the parasites and have low similarity with their human orthologue, they have been proposed as attractive therapeutic targets. Here, we have developed two yeast-based assays that allow an inexpensive high-throughput screening of TrypHRG inhibitors within a cellular context. Methods: We first assessed that Leishmania major, Leishmania donovani and T. brucei HRG proteins were heterologously expressed in the digestive vacuole membrane of a mutant heme auxotrophic yeast strain. Here, TrypHRG imports hemoglobinderived heme into the cytosol, allowing mutant yeast to grow in the presence of low hemoglobin concentrations and promoting the activity of hemeproteins such as catalase, which was used as a reporter of cytosolic heme levels. Results: In the presence of a TrypHRG inhibitor, both catalase activity (test 1) and yeast growth (test 2) were diminished, being easily monitored. The assays were then tested on a pilot scale for HTS purposes using a collection of repurposing drugs and food antioxidants. Some of the TrypHRG inhibitors identified in yeast presented strong trypanocidal and leishmanicidal activity in the submicromolar range, proving the potential of this approach. Conclusions: Cumulatively, it was shown that the inhibition bioassays developed were robust and appli- cable to large-scale HTS.
Keywords: Leishmania; Trypanosoma; Trypanosomatid parasites; Heme; HTS Screening; HRG transporters